2018
DOI: 10.1021/acsomega.8b00510
|View full text |Cite
|
Sign up to set email alerts
|

Novel Conducting and Biodegradable Copolymers with Noncytotoxic Properties toward Embryonic Stem Cells

Abstract: Electroactive biomaterials that are easily processed as scaffolds with good biocompatibility for tissue regeneration are difficult to design. Herein, the synthesis and characterization of a variety of novel electroactive, biodegradable biomaterials based on poly(3,4-ethylenedioxythiphene) copolymerized with poly(d,l lactic acid) (PEDOT-co-PDLLA) are presented. These copolymers were obtained using (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol (EDOT-OH) as an initiator in a lactide ring-opening polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 95 publications
0
40
0
Order By: Relevance
“…Then, PPy-g-PCL was achieved by oxidative polymerization of Py-g-PCL monomer. Recently, Sliva et al [73] reported a series of copolymer of PEDOT with poly(d,l-lactic acid) (PEDOT-co-PDLLA) as a scaffold materials for neuronal tissue engineering. The copolymers were synthesized via subsequent EDOT−PDLLA macromonomer production using ROP of lactide in presence of EDOT-OH, followed by chemical copolymerization of EDOT monomers.…”
Section: Covalent Grafting Of Conducting Polymersmentioning
confidence: 99%
“…Then, PPy-g-PCL was achieved by oxidative polymerization of Py-g-PCL monomer. Recently, Sliva et al [73] reported a series of copolymer of PEDOT with poly(d,l-lactic acid) (PEDOT-co-PDLLA) as a scaffold materials for neuronal tissue engineering. The copolymers were synthesized via subsequent EDOT−PDLLA macromonomer production using ROP of lactide in presence of EDOT-OH, followed by chemical copolymerization of EDOT monomers.…”
Section: Covalent Grafting Of Conducting Polymersmentioning
confidence: 99%
“…The new amphiphilic heterografted copolymer was synthesized by combining the so-called "macromonomer" or "grafting through" technique, 28,29,[33][34][35] via oxidative polycondensation reaction of an equimolecular mixture of two thiophene-ended macromonomers (Scheme 1), a classical method for CPs chemical synthesis. The hydrophilic macromonomer, Th-PEG, was synthesized by chain-end functionalization method, through Steglich esterification of hydroxyl group of PEG2000 (Scheme 1A), being the first time it has been reported.…”
Section: Molecular Design and Structural Characterization Of Pth-g-(pmentioning
confidence: 99%
“…The first step of the synthesis was to obtain an electroactive macromonomer of EDOT-PDLLA, which was developed in our previous study 34 (Figure 1a). Briefly, 3,6-dimethyl-1,4-dioxane-2,5-dione (2.76 g, 20 mmol), hydroxymethyl EDOT (100 mg, 0.6 mmol) and tin(II)-2-ethylhexanoate (0.016 mL, 0.05 mmol) were stirred at 110 °C with 7 mL of toluene for 24 h. The solvent was removed by distillation under reduced pressure (2000 Pa, 60 °C).…”
Section: Synthesis Of the Au/pedot-pdlla Nanocompositesmentioning
confidence: 99%
“…The polymerization of this electroactive macromonomer was tried by electrochemical methods, but (i) only oligomers were formed due to the high solubility in organic solvents, and (ii) no electroactive properties were found. Additionally, the chemical synthesis of a new PEDOT-co-PDLLA copolymer 34 with conductivity, biodegradability and noncytotoxicity properties tested for embryonic stem cells (E14.tg2a) was reported by using the electroactive macromonomer.…”
Section: Introductionmentioning
confidence: 99%